2011
DOI: 10.1259/dmfr/58488265
|View full text |Cite
|
Sign up to set email alerts
|

Cemento-osseous dysplasia of the jaw bones: key radiographic features

Abstract: Objective: The purpose of this study is to assess possible diagnostic differences between general dentists (GPs) and oral and maxillofacial radiologists (RGs) in the identification of pathognomonic radiographic features of cemento-osseous dysplasia (COD) and its interpretation. Methods: Using a systematic objective survey instrument, 3 RGs and 3 GPs reviewed 50 image sets of COD and similarly appearing entities (dense bone island, cementoblastoma, cemento-ossifying fibroma, fibrous dysplasia, complex odontoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
75
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(119 citation statements)
references
References 17 publications
16
75
2
1
Order By: Relevance
“…In this study, CODs were more common in women, with a mean age between the 5th and 6th decades of life, similar to the findings of other studies (3,11,12). The present study did not include the data on ethnicity of each patient because they were not recorded in the radiological reports, although most studies have found higher predilection for black patients (3,4,13).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, CODs were more common in women, with a mean age between the 5th and 6th decades of life, similar to the findings of other studies (3,11,12). The present study did not include the data on ethnicity of each patient because they were not recorded in the radiological reports, although most studies have found higher predilection for black patients (3,4,13).…”
Section: Discussionsupporting
confidence: 88%
“…These findings are similar to those of previous reports (3,12) and are in disagreement with the data found by de Noronha Santos Netto et al (11) who, out of a total of 100 cases of COD, found 65 florid COD, 18 focal COD and only 17 periapical COD. This result may be related to the fact that florid COD is more often symptomatic than the other types of COD, besides their study included only cases with histopathological diagnosis.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although the etiology and the triggering factors were not identified [8], Florid osseous dysplasia could result from abnormal activity of the periodontal ligament explaining its near-exclusive location in the dental region, with cemento-osseous lesions identified in relation to dental apices and dental anatomy in radiographic examinations [9]. It is generally asymptomatic and the teeth in relation to the lesions are unaffected Med Buccale Chir Buccale 2017; 23:196-199 A.-C. Melka et al [10][11][12]. Florid osseous dysplasia becomes symptomatic when lesions are accompanied by infection, or if cortical fenestrations occur [3].…”
Section: Commentsmentioning
confidence: 99%
“…The diagnosis is radiological with the presence of mixed multilobular well-defined images of the alveolar bone, respecting the basilar bone. Any rhizalysis are reported [11]. Other diagnoses are ossifying fibroma, Paget disease, diffuse chronic osteomyelitis, Gardner syndrome, and endodontic lesions [12].…”
Section: Commentsmentioning
confidence: 99%